Pelatihan “Giving and Asking for Direction” untuk Mengenalkan Kearifan Budaya Lokal Melalui Film Pendek : Kegiatan ABDIMAS di SMA Fons Vitae 1 Jakarta - Putri Rindu Kinasih; Junita Junita (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Currently, the skills needed to advance a tourist area are influenced by the availability of human resources who can speak English and understand local culture well. Unfortunately, improving English proficiency remains a challenge. Additionally, another issue appears as the Alpha generation is exposed to a great deal of English-language social media content; however, this does not appear to be directly correlated with an improvement in their English proficiency. It appears that the English Club instructors at SMA Fons Vitae 1 Jakarta were also aware of these two problems. Therefore, on September 11, 2025, an ABDIMAS activity entitled "Giving and Asking for Direction" training was held with the production of a short film. This activity was attended by 15 participants, 10 boys and 5 girls, a combination of students from grades 10 and 11. The results of the training showed that the pre-production process of making a short film provided a space for participants to recognize and explore Indonesian cultural heritage. Furthermore, the production process of making a short film made participants not afraid of speaking English. In the post-production process, participants can also edit parts of the video that are less than satisfactory because they can re-record if there are errors in pronunciation and grammar.